Estrategia para fortalecer la formación matemática de los estudiantes de licenciatura de matemáticas en solución de problemas no rutinarios en la ciudad de Tunja - Carrillo Chaparro, José Alberto (Universidad Antonio Nariño, 2022)
Understanding that the didactics of mathematics attend, structure, and organize the construction of theoretical models to describe and explain the different aspects related to the teaching-learning process of mathematics within the framework of a specific educational system, the training of Bachelors in Mathematics and knowing that the didactic and pedagogical component is a transversal aspect that must be worked implicitly within all the academic spaces of formation of a Mathematics Graduate of the Pedagogical and Technological University of Colombia, where didactic or methodological strategies are designed, elaborated and applied. that contribute to a significant training of future Mathematics teachers where apart from remembering, understanding and applying a series of mathematical concepts, contextualized situations exist not only in mathematics but also in real, manipulative and recreational contexts that potentiate skills of a cognitive level High native, where the student must analyze, justify, evaluate and create alternative solutions to non-routine mathematical situations. For this reason, the research proposes a system of activities that have a pedagogical and didactic structure based on the theory of problem solving, particularly in the challenging problems associated with arithmetic, algebraic and geometric thoughts. Carrying out the activities in the different synchronous class sessions allows students to understand the concepts, heuristics and metacognitive processes that are related to each of the problems that will be developed in the training workshop sessions, as well as providing them with conceptual tools. and practices for the elaboration of class plans based on non-routine problems in arithmetic, algebraic and geometric thoughts for basic education